THOUGHT TASAWUF IBNU ATHAILLAH - -, Mustaqim (Mahad Aly Al Fithrah Press, 2016)
Sufism is a very essence to form a person's attitude or morals in the service of God. when running every human activity can not be separated from the two forces of influence namely lahiriyah and batainiyah. When the two forces are equally sharpened then the power of batiniyah will be greater in affecting one's life. So in the science of tasawuf more emphasis on the spiritual aspect of the body because many scholars tasawuf assess kebehagiaan will be felt when the condition of the heart is clean from the influence of lust until every activity is always worth worship. Achievement of the highest level in running a worship of course must follow several methods to achieve makrifat. In this case the author takes the point of thinking lived by Ibn Athaillah who can lead someone to know his Lord more closely. He is a mursid in the greatest line of Sadziliyah tatekat. His thinking is easily accepted by all circles because it is easy to understand and not contrary to shariat or the circumstances of a person. The tarekat must be disciplined in running the shariat which has been led by the Prophet, A disciple should not abandon his profession when running the path, A disciple may be a billionaire origin of the treasure is not busy his heart to always dzikir to Allah SWT, always train the soul by constantly multiply fasting, , alms and Zuhud apply to the world means emptying the heart from other than Allah and not be deceived by the world. It is easy to understand the tashawuf Ibn Ataha Allah that is to do Taqwa to Allah SWT is inward and inward, Says and acts in accordance with As-Sunnah, Rejects the power of beings in creation and arrangement, Whether in a state of little or much thanks to God.